Design of High Efficiency Illumination for LED Lighting. (24th November 2013) - Chang, Yong-Nong; Cheng, Hung-Liang; Kuo, Chih-Ming
Abstract : A high efficiency illumination for LED street lighting is proposed. For energy saving, this paper uses Class-E resonant inverter as main electric circuit to improve efficiency. In addition, single dimming control has the best efficiency, simplest control scheme and lowest circuit cost among other types of dimming techniques. Multiple serial-connected transformers used to drive the LED strings as they can provide galvanic isolation and have the advantage of good current distribution against device difference. Finally, a prototype circuit for driving 112 W LEDs in total was built and tested to verify the theoretical analysis.